COOPERATION BETWEEN THE BUKHARA EMIRATE AND THE KOKAND KHANATE - Xolikulov A. B. (TARIXIY TADQIQOTLAR, 2026)
In this article, based on primary sources as well as the works of domestic and foreign historians, the diplomatic relations between the Bukhara Emirate and the Kokand Khanate are examined, along with the contradictions that existed between them, the specific features of Bukhara–Kokand relations during the reigns of Emir Shahmurad and Emir Haydar, the issue of Uratyube, the military campaigns of Emir Nasrullah against the Kokand Khanate, the reasons for their emergence, and the pretexts that served as triggers for the outbreak of hostilities.